Научная проблема обеспечения рационального сочетания устойчивости и управляемости летательного аппарата военного назначения на основе синтеза аэродинамической компоновки на этапе концептуального проектирования - Ковтонюк, Игорь Борисович (НТУ "ХПИ", 2015)
Розглянуто наукову проблему забезпечення раціонального поєднання стійкості і керованості літальних апаратів військового призначення на основі синтезу аеродинамічного компонування на етапі концептуального проектування. Визначено напрямки та етапи вирішення даної наукової проблеми.

The scientific problem of ensuring the rational combination of stability and controllability military aircrafts based on the synthesis of aerodynamic arrangement at the stage of conceptual design is considered. The directions and stages of this scientific problem are determined.
The scientific problem of ensuring the rational combination of stability and controllability military aircrafts based on the synthesis of aerodynamic arrangement at the stage of conceptual design
Keywords: научно-методический аппарат; летно-технические характеристики; аэродинамические характеристики